Examining the Depiction of Domestic Violence in Popular Adult Fiction: A Review of Six Novels - Finley, Laura (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Popular culture is a powerful teacher about a variety of peace, conflict and justice-related issues. As such, it is a tool for peacebuilding education (Brantmeier, 2007). Scholars have long recognized the importance of using literature and music to critique war, to draw attention to inequalities, and alternately, to promote peace (Ahlkvist, 1999, 2001; Brkich, 2012; Brozo, Walter, & Placker, 2002; Franzak & Noll, 2006; Noddings, 2006; Wolk, 2009; Wright & Kowalczyk, 2000). As an alternative or augment to traditional text books, popular culture can help reach students who learn in different ways (Gardner, 2006), and can help to develop emotional intelligence (Goleman, 2006). Students who are bored with typical texts and lectures may not only find popular culture more interesting, but they may also be able to learn more from it because they see its relevance in their lives (Buckingham, 2014). Violence is ubiquitous and is notonly reflected in popular culture but generated through it as well (Giroux, 2013). It is imperative, then, that peace educators help promote media literacy that examines various forms of popular culture through a critical lens (Buckingham, 2014).